Machine learning algorithm for activity‐aware demand response considering energy savings and comfort requirements. Issue 5 (12th October 2020) - Zhang, Yue; Srivastava, Anurag. K.; Cook, Diane
Abstract : Due to the high cost of peak hour power generation and a push towards sustainability, the need for demand response (DR) is increasing. Compared to commercial‐level DR, residential‐level DR is more challenging. Residents are reluctant to participate, and DR controllers lack sufficient real‐time activity information to balance energy savings with residents' need for comfort and convenience. To address the above challenges, we propose a sensor data‐driven activity‐based controller for heating, ventilation, and air conditioning devices. Using our proposed novel strategy, resident activities are recognized in real‐time through a random forest machine learning approach. Integrating activity information and forecasted electricity pricing, the proposed controller can simultaneously reduce energy consumption for sustainability and maintain resident constraints for comfort based on recognized activities. Results demonstrate the superiority of the proposed approach.